Managing condensationand mould in Malaysia - Muhammad Syukri Imran, Abdullah; Khairul Azmy, Kamaluddin (Step Communications Ltd, 2024)
Dr Muhammad Syukri Imran Abdullah, registered professional engineer with BEM Malaysia, and Dr Khairul Azmy Kamaluddin, president of Biomedical Engineering Association of Malaysia (BEAM), look at the strategies Ministry of Health Malaysia is using to manage condensation-related mould issues in healthcare facilities, showcasing how they prioritise health and safety while navigating moisture control complexities.